Autophagy flux inhibition mediated by lysosomal dysfunction participates in the cadmium exposure‐induced cardiotoxicity in swine. (14th March 2022) - Zhao, Xia; Shi, Xu; Yao, Yujie; Li, Xiaojing; Xu, Shiwen
Abstract: Cadmium (Cd), a common toxic heavy metal, is believed as a risk factor for the induction and progression of cardiovascular disease. Autophagy is a highly ordered intracellular lysosomal‐mediated degradation pathway that is crucial for protein and organelle quality control. Autophagy dysfunction could develop exacerbated cardiac dysfunction. However, the role of autophagy in Cd exposure‐induced cardiotoxicity remains largely unknown. In this study, the Cd‐induced swine cardiotoxicity model was established by feeding with a CdCl2 suppled diet (20 mg Cd/kg diet). The results showed that Cd exposure increased the expression of endoplasmic reticulum stress‐related genes (GRP78, GRP94, IRE1, XBP1, PERK, ATF4, and ATF6), increased the expression of Ca 2+ release channels IP3R and RYR1 and decreased the expression of Ca 2+ uptake pump SERCA1. Cd exposure upregulated the expression of autophagy‐related genes (CAMKKII, AMPK, ATG5, ATG7, ATG12, Beclin1, LC3‐II, and P62) and downregulated mTOR expression. Cd exposure inhibited the expression of V‐ATPase and cathepsins (CTSB and CTSD), and increased the expression of cathepsins in cytoplasm. Cd exposure decreased the colocalization of autophagosome and lysosome. This study revealed that autophagy flux inhibition caused by lysosomal dysfunction participates in the cardiotoxicity induced by Cd exposure in swine.